Exploration of Chirality and Achirality of Self‐Assembled Monolayer Formed by Unsymmetrically Substituted Fluorenone Derivative at the Liquid/Solid Interface. Issue 1 (27th November 2017) - Hu, Yi; Miao, Kai; Dong, Meiqiu; Xu, Li; Zha, Bao; Miao, Xinrui; Deng, Wenli
Abstract: The self‐assemblies of 2‐decyloxy‐7‐pentadecyloxy‐9‐fluorenone (DPF) are characterized by scanning tunneling microscopy at the liquid/solid interface. Achiral Dimer and chiral S‐like structures are observed in 1‐octanoic acid. The solvent molecule takes part in the self‐assembly via forming COOH⋯OC and COOH⋯COOH hydrogen bonds. When 1‐phenyloctane and n ‐tetradecane are used as the solvents, DPF self‐assembles into chiral Z‐like structure, which are classified into Types I–IV according to the packing styles. For the purpose of exploring the effect of solvent and the competition between these three structures, the self‐assemblies of DPF in mixed solvents and on dry surface are investigated. The results show that S‐like structure is preferred in mixed solvents, while the Z‐like structure has priority when the function of solvent is excluded. DPF molecule shows polarity thus dipole−dipole interaction plays significant roles on forming stable adlayers by forming antiparallel dipole pairs. Furthermore, density functional theory calculation is performed to reveal the driving forces of hydrogen bonds and van der Waals interactions. In light of the popularity of studying chirality at the liquid/solid interface, it is believed that the findings will provide implications for designing chiral systems and will promote the exploration of self‐assembly in the field of surface science. Abstract : Induction and fabrication of chirality have received intense attention in natural science because chirality affects the performance of many chemical, physical, and biological systems. In this work asymmetrically substituted fluorenone derivative which possesses solvent‐induced chiral and achiral self‐assemblies at the liquid/solid interface, thus be potential to be used in nanoscience and nanotechnology are explored.